Soybean oil biodiesel production in Argentina case study - Hilbert, Jorge Antonio (2014)
Soybean production is immersed within a productive system that cannot be analyzed on its own. A number of political and market factors, both nationally and internationally, explain the development and growth of soybean production throughout the globe. In the case of Argentina, the evolution of the agricultural system of soybean production has been characterized by continuous technological improvement. This has changed the whole agricultural system and set the base for societies growing demands for environmental and socially responsible goods. An advancement of regulatory context has allowed a better control of the future development of land usage. In Argentina’s case the Law of minimum budget (Law on Conservation of Native Forest) is an example towards that direction. The Argentinean soy industry is one of the most dynamic economic sectors of the country, generating almost 30% of the external currencies income due to exports and representing almost 30% of GDP from the agro-industrial sector. Argentina is the world’s leading exporter in soybean oil, soy meal and soy biodiesel and the third one in soybeans. The future expansion of this industry in the country is heavily dependent on internal and external changes in policies and is thus uncertain. A complete LCA study following EU procedures were performed. Several studies have been carried over in order to clerarly calculate according to international methodologies the GHG emitions of Argentine biodiesel. Since the country has different agroecosystems and distances from the ports can be very different complete research studies were carried over on different regions of the country With respect to GHG emissions (Kg CO2 eq/km), at a global level it could be said that The scenario that showed more GHG emissions was South East of Bs.As. (0,0447 Kg CO2 eq/km). Comparatively and percentage with conventional diesel, its reductions of GHG emissions were of 75,5 %. Recent studies over very precise figures from farm to port on regional plants gave reduction percentages over 70 %.